1965
DOI: 10.1115/1.3689109
|View full text |Cite
|
Sign up to set email alerts
|

Measured Temperature Profiles Within the Superheated Boundary Layer Above a Horizontal Surface in Saturated Nucleate Pool Boiling of Water

Abstract: Temperature measurements were made within the superheated boundary layer above and adjacent to a horizontal heating surface in saturated, nucleate, pool boiling of water. A microthermocouple probe was used to measure the average temperature profiles and the temperature fluctuations within the boundary layer at heat fluxes from 1000 to 40,000 Btu/hr-sq ft. Correlations are presented for the “extrapolated” thickness of the boundary layer (δ) as well as the temperature distribution within it. It was found that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1

Year Published

1966
1966
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(8 citation statements)
references
References 0 publications
0
7
1
Order By: Relevance
“…It was observed that the bubble is surrounded by the superheated layer, which was stretched by the growing bubble during its growth period, and the bubble remained surrounded by the superheated layer even after departure. The estimated wall thermal boundary layer thickness in saturated boiling was about 1.3 mm, which is about 4 times larger than the value measured by [38] . Additionally, they observed a superheated liquid jet in the wake region of the rising bubble.…”
Section: Heat Transfer Mechanismscontrasting
confidence: 57%
See 1 more Smart Citation
“…It was observed that the bubble is surrounded by the superheated layer, which was stretched by the growing bubble during its growth period, and the bubble remained surrounded by the superheated layer even after departure. The estimated wall thermal boundary layer thickness in saturated boiling was about 1.3 mm, which is about 4 times larger than the value measured by [38] . Additionally, they observed a superheated liquid jet in the wake region of the rising bubble.…”
Section: Heat Transfer Mechanismscontrasting
confidence: 57%
“…Before discussing the mechanisms, it is important to shed some light on the thermal boundary layer characteristics and the temperature field around the bubble in saturated boiling of water, which is a key variable in bubble growth models. Marcus and Dropkin [38] measured the liquid temperature at vertical locations on a horizontal copper surface using a micro-thermocouple probe in the heat flux range 3.6 -126 kW/m 2 . It was found that the boundary layer was linear only up to 0 .…”
Section: Heat Transfer Mechanismsmentioning
confidence: 99%
“…Measurements of temperature fields near heating surfaces in pool boiling have been conducted by Marcus and Dropkin [3], Lippert and Dougall [4], Fujita et al [5], Bobst and Colver [6], Afgan [7], and Hinata et al [8] for saturated boiling. In subcooled boiling, Wiebe and Judd [9] measured temperature profiles up to 58 K subcooling, with measurements limited to an isolated bubble region at low heat fluxes, up to 0.32 MW/m 2 , and not at higher heat fluxes where large vapor masses are formed.…”
Section: Introductionmentioning
confidence: 99%
“…1 compares the authors' water correlation from their Fig. 11 of heat transfer coefficient, h, versus sublayer thickness, S, to that of Bobst and Colver [1] and Marcus and Dropkin [2], I would certainly concur with the authors that the slight displacement of one curve from another is the result of differences in physical and chemical properties of the boiling surface, which, in turn, affects nucleating characteristics. It is of particular note that while the authors did find a break in their curve (denoting a transition from natural convection to nucleate boiling) at approximately h = 600 Btu/(hr)(sq ft) their data did not extend to high enough heat fluxes to determine the existence of another break such as shown by the data of Bobst and Colver.…”
mentioning
confidence: 61%